Activation of complement component 3 is associated with airways disease and pulmonary emphysema in alpha-1 antitrypsin deficiency. Issue 4 (20th January 2020) - O'Brien, Michael E; Fee, Laura; Browne, Niall; Carroll, Tomás P; Meleady, Paula; Henry, Michael; McQuillan, Karen; Murphy, Mark P; Logan, Mark; McCarthy, Cormac; McElvaney, Oliver J; Reeves, Emer P; et al.
Abstract : Introduction: Alpha-1 antitrypsin (AAT) deficiency (AATD) is associated with early onset emphysema. The aim of this study was to investigate whether AAT binding to plasma constituents could regulate their activation, and in AATD, exploit this binding event to better understand the condition and uncover novel biomarkers of therapeutic efficacy. Methods: To isolate AAT linker proteins, plasma samples were separated by size exclusion chromatography, followed by co-immunoprecipitation. AAT binding proteins were identified by mass spectrometry. Complement turnover and activation was determined by ELISA measurement of C3, C3a and C3d levels in plasma of healthy controls (n=15), AATD (n=51), non-AATD patients with obstructive airway disease (n=10) and AATD patients post AAT augmentation therapy (n=5). Results: Direct binding of complement C3 to AAT was identified in vivo and in vitro. Compared with healthy controls, a breakdown product of C3, C3d, was increased in AATD (0.04 µg/mL vs 1.96 µg/mL, p=0.0002), with a significant correlation between radiographic pulmonary emphysema and plasma levels of C3d (R 2 =0.37, p=0.001). In vivo, AAT augmentation therapy significantly reduced plasma levels of C3d in comparison to patients not receiving AAT therapy (0.15 µg/mL vs 2.18 µg/mL, respectively, p=0.001). Discussion: Results highlight the immune-modulatory impact of AAT on the complement system, involving an important potential role for complement activation in disease pathogenesis in AATD. The association between plasma C3d levels and pulmonary disease severity, that decrease in response to AAT augmentation therapy, supports the exploration of C3d as a candidate biomarker of therapeutic efficacy in AATD.